Training Transfer: a Moderator of Entrepreneurial Performance Determinants - Genty Kabiru Ishola (Economics and Business)
The present study examines the moderating effect of training transfer on the determinants of entrepreneurial performance among owners of micro, small and medium enterprises (MSMEs) in Lagos State, Nigeria. The study adopts a quantitative approach using a cross-sectional descriptive survey while Cochran (1977) formula for sample size determination is used to calculate the sample size. Structural Equation Modelling (SEM) approach and Multi-Group Analysis are applied to test the stated research hypothesis. Prior to full use of the model, the researcher ensures that the model meets the acceptable goodness-of-fit indices: X2 (CMIN) = 387.238 (DF = 196), Relative X2 (CMIN/DF) = 1.976, AGFI = 0.870, GFI = 0.899, CFI = 0.939, IFI = 0.939, TLI = 0.928 and RMSEA = 0.056. The structural model has revealed that the relationship between personal qualities, business competences, and environmental factors are moderated by training transfer in the study with measurement residual X2 greater than unconstrained X2 based on model comparison output ΔX2 (CMIN) = 140.931; Δdf = 57; p = 0.000. Therefore, there is presence of moderation effect of training transfer on the determinants of entrepreneurial performance in the overall model.